Ocena trafności krótkookresowych prognoz koniunktury gospodarczej przedsiębiorstw budowlanych - Kowalewski, Grzegorz (Estimate of Propriety of Short-Run Forecast Activity of Situation of Economic Construction Industrial Enterprise, 2006)
Researching of quality of forecast formulated is purpose of article by directors of construction industrial enterprises in Poland. In weak situation of propriety of forecast try (taste) to find (to be placed) it reason. Two meters ex post employ for estimate of accuracy of forecast fast: Theil and for differences divergence. Article is based on empirical research. Results of business condition surveys are base of estimate of forecast.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 228-235